2018
DOI: 10.2139/ssrn.3171957
|View full text |Cite
|
Sign up to set email alerts
|

Blood Type and Blood Donation Behaviors: An Empirical Test of Pure Altruism Theory

Abstract: We examined whether the knowledge that your private donation has a large number of potential recipients causes you to give more or less. We found that the people with blood type O are more likely to have donated blood than those with other blood types, by using a Japan's nationally representative survey. This association was found to be stronger in a subsample of individuals who knew and believed that blood type O can be medically transfused into individuals of all blood groups. However, we found that blood ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Subsection IIIA. 24 We also adopt a specification with X squared instead of I[ X j ≥ 4] to account for the nonlinearity, and most of our results also remain unchanged. We estimate equation 5using ordinary least squares (OLS).…”
Section: Identification Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsection IIIA. 24 We also adopt a specification with X squared instead of I[ X j ≥ 4] to account for the nonlinearity, and most of our results also remain unchanged. We estimate equation 5using ordinary least squares (OLS).…”
Section: Identification Strategymentioning
confidence: 99%
“…Again, we plot the changes in residual of transformed price regressed on a constant term (year fixed effect). Each 24 Furthermore, we draw on Hansen (1999) to estimate a regression kink model with an unknown location of the kink. We find that the location of the kink is X = 3.30 for a default trimming parameter of 0.15 and X = 5.09 for the parameter 0.20 for the short-term analysis (2011-2012).…”
Section: Identification Strategymentioning
confidence: 99%
“…It is possible that when a CR-M campaign is not conspicuous, consumers behave altruistically out of pure compassion for others. While we did not measure consumers' motivations to donate in this context, the concept of pure altruism (Owens et al, 2018;Sasaki et al, 2018) may help explain this behavior. Overall, the results for H2-H4 demonstrate that high-end brands benefit the most when a brand's CR-M campaign are conspicuous, while lowend brands may not reap benefits of this marketing practice.…”
Section: Discussionmentioning
confidence: 99%
“…lowend brands), they derive no social or ego-enhancement benefits (Grace and Griffin, 2006). Instead, consumers may be motivated to donate to charities out of compassion for others, in acts classified as pure altruism (Owens et al, 2018;Sasaki et al, 2018). In such cases, the motivation to donate stems from the desire to help others; thus, the brand level of the item becomes irrelevant.…”
Section: Effect Of Conspicuous Compassion On Consumers' Responsesmentioning
confidence: 99%
“…Previous findings on blood group differences in donation rates are somewhat mixed. Though some studies found no association between blood groups and donation rates, indicating that blood donation is driven by various motivations (Wevers, Wigboldus, De Kort, Van Baaren, & Veldhuizen, 2014;Wildman & Hollingsworth, 2009), others found O-donors to have a higher chance of ever donating (Sasaki, Funasaki, Kurokawa, & Ohtake, 2020), O-negative donors to have a higher chance of returning for a subsequent donation (Gemelli, Hayman, & Waller, 2017), and being a high-frequency donor (Veldhuizen, Doggen, Atsma, & De Kort, 2009). More specifically, Sasaki and colleagues (2020) found that the positive association between O-blood group and blood donations was especially present when donors knew that their blood could be used to treat all patients in need of blood.…”
Section: Altruism As a Motivation Of Blood Donationmentioning
confidence: 99%